2015
DOI: 10.1055/s-0035-1568871
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Endonasal Reconstruction of Skull Base: Repair Protocol

Abstract: Background?Endoscopic endonasal skull base reconstructions have been associated with postoperative cerebrospinal fluid (CSF) leaks. Objective?A repair protocol for endoscopic endonasal skull base reconstruction is presented with the objective of decreasing the overall leak rate. Methods?A total of 180 endoscopic endonasal skull base reconstructions were reviewed. Reconstructions were classified I to IV according to the reconstruction method, determined by severity of intraoperatively encountered CSF leaks fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 38 publications
0
8
1
1
Order By: Relevance
“…In our study, we found that patients who did not exhibit intraoperative CSF leak did not develop a postoperative leak also. This is in contrast to a significant 2% of patients undergoing type II repair developing postoperative leak in a study conducted by Dehdashti et al [6]. One important difference in the method of type II repair between the two studies is the additional use of a nasoseptal flap in our study.…”
Section: Csf Leak Repair and Postoperative Csf Leakcontrasting
confidence: 81%
“…In our study, we found that patients who did not exhibit intraoperative CSF leak did not develop a postoperative leak also. This is in contrast to a significant 2% of patients undergoing type II repair developing postoperative leak in a study conducted by Dehdashti et al [6]. One important difference in the method of type II repair between the two studies is the additional use of a nasoseptal flap in our study.…”
Section: Csf Leak Repair and Postoperative Csf Leakcontrasting
confidence: 81%
“…22,23 Thus far, skull base surgeons have been unable to consistently achieve these goals, which is reflected on the myriad of materials and techniques used by different groups, and the fact that most postoperative complications in endoscopic skull base surgery derive from failure of skull base reconstruction. [1][2][3][4][5][6] Platelet concentrates have been used for decades to promote healing in different tissues, 9,11 with L-PRF being the latest of those products to be described. 24 Yielded by natural polymerization of circulating fibrin, the resulting mesh is similar to that formed during normal hemostasis, 12,25 trapping circulating growth factors and cytokines, 8,12 and containing >80% of platelets and >50% of leukocytes of the original blood sample embedded into it.…”
Section: Discussionmentioning
confidence: 99%
“…Grafts are most often held in place against the skull base with cellulose strips, tissue glues, or gelfoam, though the use of dural sealant with NSFs is not necessary and may in fact be detrimental. 7,[33][34][35][36] For cases involving vascular pedicled flaps or tenuous repairs, additional reinforcement may be provided with a nasal tampon, bioresorbable packing (eg, NasoPore), or balloon catheter, which may be removed later. 30,34 4 | INTRANASAL VASCULAR PEDICLED…”
Section: Multilayer Closure Foundation Terminology and Principlesmentioning
confidence: 99%